Agricultural Cooperatives and Members’ Access to Financial Services in Makawanpur, Nepal - Bidari, Sandesh; Khanal, Vishnu (International Research Journal of MMC, 2026)
This research aims to investigate the role of agricultural cooperatives in promoting the accessibility of financial services to their members. To achieve the objective, we adopted a survey research design with a total of 123 agricultural cooperative members who were asked to fill out the questionnaire which included 13 items measured on a five-point Likert scale, ranging from 1 (strongly disagree) to 5 (strongly agree). Descriptive analysis (Median=4) showed a positive perception of cooperative members on the services of agricultural cooperatives. Independent samples Mann-Whitney U test (Sig. .445) showed that there was no significant difference in the median scores of male and female members regarding their perceptions of the role of agricultural cooperatives in improving access to financial services. The research findings showed the both male and female agricultural cooperative members’ positive perceptions on the financial services provided by the cooperatives. The financial services include the accessibility of credit services, the ease of loan repayment, the fairness of interest rates, the affordability of the cost of membership, the support for vulnerable groups, and the overall perception of agricultural cooperatives. The agricultural cooperatives were seen to be fair and equitable for all members regardless of gender. The study is significant as it explores how agricultural cooperatives enhance members’ access to financial services, thereby supporting rural livelihoods, economic empowerment, and sustainable development.